Two new species of Anisocyrta Foerster (Hymenoptera: Braconidae: Alysiinae) from China - Yao, Junli; Kula, Robert R.; Chen, Jiahua (Zootaxa, 2018)
Two new species of the genus Anisocyrta Foerster, 1863, from China are described and illustrated: Anisocyrta xiaoliyaoae Yao, sp. n. and Anisocyrta cvanachterbergi Yao, sp. n. Anisocyrta is reported from China for the first time. A key to the Palearctic species of the genus Anisocyrta is provided based on the keys of van Achterberg (1986) and Belokobylskij (1998). Type specimens of the two new species are deposited in the Beneficial Insects Institute Collection, Fujian Agriculture and Forestry University, Fuzhou, China (BIIC).